OPTIMASI KONDISI FERMENTASI PADA PEMBUATAN MINYAK KELAPA (Cocos nucifera L) DENGAN MENGGUNAKAN Saccharomyces cerevisiae - Willy Pranata Widjaja; Bonita Anjarsari (Faculty of Agricultural Technology, University of Jember, 2014)
Research has been done on the optimization of fermentation conditions for the manufacture of coconut oil from coconut meat slurry using Saccharomyces cereviceae. The purpose of this study is to determine the ratio of oil and water, stirring speed and concentration of inoculum S. cerevisiae the quantity and quality of the oil produced from the coconut meat slurry fermentation method. Stages of the process include the making of starters and age determination of S. cerevisiae, inoculation, fermentation and filtration. Best products achieved at inoculum concentrations of 14% with a speed of 200 rpm and produces yield of 35.77%. Starter culture is the optimum time of 30 hours at 35°C by the number of cells 185 x 105 cells / ml. Temperature and time of fermentation was significant effect on yield and starch content but does not affect the saponification numbers, levels of free fatty acids (FFA), iodine number.Keywords: fermentation condition, coconut meat slurry, coconut oil, S. cerevisiae, yield, starch content